Mixed convection in a lid-driven cavity in the presence of magnetic field with sinusoidal heating - Bakar, Norhaliza Abu; Roslan, Rozaini; Sazeli, Zul Afiq; Salim, Nur Raidah (Semarak Ilmu Publishing, 2024)
Understanding mixed convection in engineering applications such as heat exchangers, electronics cooling devices, and solar energy collectors have urged researchers to investigate this phenomenon deeper. This study investigates the fluid flow and heat transfer pattern in a two-dimensional (2D) rectangular cavity with sinusoidal heating on the moving top lid numerically. The bottom wall is kept cool while the vertical walls are insulated. The effect of Hartmann number, Ha on the thermal characteristics and fluid flow are analyzed for Richardson number, Ri = 1 which indicate mixed convection dominated regime. The governing equations are solved numerically using a SIMPLE algorithm with the finite volume method. The numerical results are displayed in streamlines and isotherms plots. The value of the Nusselt number indicating the heat transfer rate is also discussed. It is found that Ha has a significant effect on the heat transfer process and fluid flow. It can be seen clearly when the value of Ha = 30, the rate of heat transfer dropped significantly on the cold wall. Generally, the heat transfer rate decreases with the increase of Ha. © 2024, Semarak Ilmu Publishing. All rights reserved.